2019
DOI: 10.1002/aisy.201900115
|View full text |Cite
|
Sign up to set email alerts
|

An Optoneuronic Device with Realistic Retinal Expressions for Bioinspired Machine Vision

Abstract: Machine vision systems rely on communication between cameras and processor modules to capture and analyze visual information. This arrangement renders them as bulky and inefficient in terms of speed and power dissipation for futuristic big data applications that involve artificial intelligence algorithms. An apparatus able to imitate the operation of biologic eyes and function as a standalone platform would therefore present the next evolutional step in machine visual perception. Neuromorphic computing is an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Photonic synapses, coupling optical sensing and synaptic plasticity, are expected to reduce power consumption and achieve ultrafast signal transmission 23,24 . The light-sensitive photosensors are similar to the photoreceptors of biological retina because they both can convert light signals to electrical signals 25 . This kind of devices, which could mimic the biologic eyes and work as a standalone platform, would pave the way for machine vision systems in the future 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photonic synapses, coupling optical sensing and synaptic plasticity, are expected to reduce power consumption and achieve ultrafast signal transmission 23,24 . The light-sensitive photosensors are similar to the photoreceptors of biological retina because they both can convert light signals to electrical signals 25 . This kind of devices, which could mimic the biologic eyes and work as a standalone platform, would pave the way for machine vision systems in the future 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The classical Pavlovian conditioning can also be verified by our synaptic device. In addition, back-gate bias could enhance or reduce memory function exhibiting similar effects of emotions 25 . Positive emotions offer a positive effect and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…[ 37 ] The memristive device was fabricated over a transparent glass substrate that allows visible radiation (light input) to reach the dielectric layer to affect defect stoichiometry. [ 23 ] The TE takes the role of the electric input, whereas the common BEs are connected to a pull‐down resistor and serve as the gate's output.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, memristive devices have been reported to produce a response to both electric and light stimulations. [ 19 24 ] In this context, Tan et al [ 25 ] proposed a hardware‐reconfigurable logic gate based on a single light‐gated memristor and demonstrated both logical disjunction (OR) and conjunction (AND) operations. However, these gates lack an inherent logical negation (NOT) function, an essential part of the spanning set for a complete logic vector space.…”
mentioning
confidence: 99%
“…In this manner, horizontalcell neurotransmitter releases under "center-surround" configurations allow for better accuracy and resolution during real-time image acquisition. This functionality was emulated, through spiking based operation, in the device proposed by Berco et al [13] as opposed to nonvolatile-state transitions. As for data processing, Hubel and Wiesel showed that mammalian neurons in the visual cortex are in fact stimulated by small regions of the visual field known as the Receptive Field.…”
Section: Introductionmentioning
confidence: 99%